PENGARUH DEBT TO ASSET RATIO DAN DIVIDEN PAYOUT RATIO TERHADAP PRICE TO BOOK VALUE PADA PERUSAHAAN SUB SEKTOR PERKEBUNAN YANG TERDAFTAR DI BURSA EFEK INDONESIA - Siti Ramalaili; Qahfi Romula Siregar (Jurnal AKMAMI (Akuntansi Manajemen Ekonomi), 2022)
The approach used is an associative approach, with the sampling criteria using the Purposive Sampling Technique, namely the sampling technique of data sources with certain considerations, so that from 19 populations only 8 samples are obtained that can be examined. Data collection techniques using documentation studies. The data analysis method used in this study used Partial Least Square (PLS). The results of the study prove that there is a significant effect between Debt to Asset Ratio on Price to Book Value, there is no significant effect between Dividend Payout Ratio on Price to Book Value, there is no significant effect between Debt to Asset Ratio on Net Profit Margin, there is no effect There is a significant difference between Dividend Payout Ratio on Net Profit Margin, there is a significant effect between Net Profit Margin on Price to Book Value, Net Profit Margin does not mediate the effect of Debt to Asset Ratio on Price to Book Value, Net Profit Margin does not mediate the effect of Dividend Payout Ratio against Price to Book Value